2020
DOI: 10.1088/1361-665x/abbc77
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of magnetorheological elastomers: a review

Abstract: Magnetorheological elastomers (MREs) are one of the categories of smart materials, whose modulus increases considerably in the presence of a magnetic field. These elastomers are prepared by dispersing magnetic micro-sized particles into a soft solid carrier medium. The main feature of these elastomers is that they change their elastic and damping properties quickly in the presence of a magnetic field. The change in properties, also known as the magnetorheological (MR) effect of MREs are dependent on various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 243 publications
1
78
0
1
Order By: Relevance
“…Having said that, for the viscoelastic behavior of MRE, other explorations on different modes of failure load such as torsional, oscillating, and sliding are getting good prospects and may also be further investigated. In addition, the recent review article 12 reported the significance of a repeat-cycle investigation involving the MRE modulus. Experimental works conducted so far were implemented shearing mode in purpose to be more realistic and reliable condition related to interaction within particles and matrix molecular structure chain 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having said that, for the viscoelastic behavior of MRE, other explorations on different modes of failure load such as torsional, oscillating, and sliding are getting good prospects and may also be further investigated. In addition, the recent review article 12 reported the significance of a repeat-cycle investigation involving the MRE modulus. Experimental works conducted so far were implemented shearing mode in purpose to be more realistic and reliable condition related to interaction within particles and matrix molecular structure chain 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study provides additional evidence to the current literature and has gone some way towards enhancing our understanding of microstructural behavior subjected to stress relaxation. Further continuous investigation of MRE is necessary to improve the properties and to understand the behavior towards the different testing and characterization procedures 12 . Therefore, it is always worthy to further investigate the shear mode deformation and long-term behavior of MRE.…”
Section: Introductionmentioning
confidence: 99%
“…The nano MR fluid has a potential to be used in applications -such as dampers in various modes (valve, shear, squeeze and combination modes) brake, semi -active controlled suspended seat, clutches, hydraulic valves, polishing devices, seals, prosthetic leg etc and some of the potential applications include automotive clutches, earthquake dampers, engine mounts, MR elastomer dampers [7][8][9]. The recent progress of MR elastomer (MRE) was presented by Bastola et al [10]. The study investigated the magnetorheological effect and various parameters on which MRE's are dependent.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of natural rubber for MREs matrices present some disadvantages. The manufacturing of natural-rubber based matrices is much more complex than the fabrication using silicone-based rubbers, due to the raw material of the matrix being in solid state, which requires specialised equipment [122].…”
Section: Magnetorheological Elastomers (Mres)mentioning
confidence: 99%